Analisis Badan Usaha Milik Desa (Bumdes) dalam Meningkatkan Kesejahteraan Masyarakat di Desa Masawoy Kecamatan Ambalau Kabupaten Buru Selatan - Hamin Belasa; Maryoni Stevanny Kainama; Theodora Florence Tomasoa (Universitas Pattimura, 2025)
Masawoy Village in Ambalau Sub-district, South Buru Regency, successfully established BUMDes Rubi to manage local potential, especially in the fisheries sector. This study aims to analyze the contribution of BUMDes in enhancing community welfare through capture fisheries (bobong) and other empowerment programs. The research applied a descriptive qualitative method using observation, interviews, and documentation. The findings indicate that BUMDes Rubi has significantly impacted local economic growth, reduced unemployment, and increased household income. It also serves as a platform for social and economic learning, particularly for village youth. Despite challenges such as lack of equipment and limited managerial capacity, community participation and local policy support are key to its success. These results highlight how community-based economic management can serve as an effective strategy for rural development. The village government is encouraged to diversify business units, enhance managerial training, and foster active public involvement to ensure program sustainability. Keywords: